BRAND IMAGE, KUALITAS PRODUK, DAN CELEBRITY ENDORSER TERHADAP MINAT BELI KONSUMEN KOSMETIK MS GLOW DI KOTA SURAKARTA - Ningsih, Lili Mulya; Suyatno, Agus; Hastuti, Indra (ITB AAS Indonesia Surakarta, 2023)
Based on the controversy (research gap) regarding the influence of Brand Image, Product Quality, and Celebrity Endorsers on Consumer Purchase Interest. This study aims to determine the effect of brand image, product quality, and celebrity endorsers on consumer buying interest in MS Glow cosmetic products in the city of Surakarta. The type of research used in this research is associative with quantitative methods, namely a research problem formulation that asks the relationship between two or more variables. The research sample is 100 respondents. The population in this study are MS Glow consumers. The method used in sampling is Nonprobability Sampling with purposive sampling technique. Data collection techniques in this study using a questionnaire. Data analysis in this study used SPSS V 25. The results of proving the solution proved that all independent variables (brand image, product quality, and celebrity endorser) had a positive effect on the dependent variable, namely consumer interest. This means that according to consumers, the three independent variables are considered important when buying MS Glow cosmetic products. The conclusion of this study is that Brand Image, Product Quality, and Celebrity Endorsers are very influential on consumer buying interest for MS Glow Cosmetic Products in Surakarta City.